Upaya Memberikan Pemahaman Tentang LGBT Dalam Perspektif Neurosience dan Prepektif Islam Pada Mahasiswa Fakultas Kedokteran Universitas Muhammadiyah Sumatera Utara - Mavianti Mavianti; Ratih Yulistika Utami; Hendra Sutysna (University of Muhammadiyah Sumatera Utara, 2019)
A good understanding is very necessary for students about LGBT so that they are able to fortify themselves not to get caught up in the relationships that can lead to LGBT. Because LGBT is indeed prohibited in religion because it gives a bad impact for the perpetrators themselves and for the community. Even according to the demands of Allah SWT and Rasulullah SAW in the Qur'an and the Hadith that LGBT is a very despicable act and includes severe violations that can damage the nature of humans as the most noble creatures of Allah SWT. Then this seminar was initiated to provide knowledge for students about LGBT from the point of view of neuroscience and from the perspective of the Islamic religion.Keywords: Paradigm, LGBT, Neuroscience, Islam Perspective